TINJAUAN ANALITIS TERHADAP MODEL PEMBANGUNAN INDONESIA - An-naf, Jullisar (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2011)
Development is generally defined as the fulfillment of individual welfare that includes per capita income, educational needs, health, quality of life including the need for self-esteem. In practice the planning and implementation of development is strongly influenced by the ideological perspective, political or development paradigm adopted by the elite in each country. Evolving paradigm begins with Classical Development Theory that was divided into various sects and schools of lower-schools of capitalism and socialism. Furthermore, also develops theories derivatives such as Dualistic Development Thesis, Structural Change Theory, Theory of Linear Stages/Stages of Economic Growth, International Dependency Theory, Counter-Revolution of Neoclassical Theory, and the latter Paradigm of Sustainable Development. Developing countries have doing many experiments with a mixture of the above theories ranging from a centralized to the schools of the liberal ideology which depends on the views adopted. The important thing to note, none of Developing Countries can solve the problem of development with only one theory unanimously adapt and intact. Because the theories of development is growing locally specific, so not entirely applicable to different situations. Since independence in 1945 Indonesia's development itself can be said to have been changing schools. But there is one distinctive feature, namely applying a liberal theories but in a situation that is very centralized and very dominant role of government. However, due to the specific local situation and deepening less recognizable, always exposed to the dead-lock situation both in the Old Order and New Order.